Environmental factors indirectly reduce phytoplankton community stability via functional diversity - Zhang, Xiaoguang; Tan, Lu; Cai, Qinghua; Ye, Lin (Frontiers in Ecology and Evolution, 2022)
The biodiversity-stability relationship is a fundamental subject of ecological research. Considerable evidence demonstrates that biodiversity can either increase or decrease stability. Most relevant research mainly focuses on grassland and forest ecosystems. The biodiversity-stability relationship in aquatic ecosystems and the underlying mechanisms remain poorly understood. To fill the gap, we conducted a year-long study on the phytoplankton of reservoir ecosystems in the Xiangxi Bay of Three Gorges Reservoir (TGR) to test the following hypotheses: (H1) phytoplankton species richness and functional diversity directly reduce phytoplankton community stability in reservoir ecosystems; (H2) nutrient enrichment and water temperature increasing directly reduce phytoplankton community stability; (H3) nutrients and water temperature indirectly reduce phytoplankton community stability via biodiversity. The structural equation model (SEM) found that functional diversity (community-weighted means of traits and functional divergence) had significant negative correlations with phytoplankton community stability (p < 0.05), while the species diversity had no significant correlation with phytoplankton community stability (p > 0.05). This finding partially supported the hypothesis H1, which suggested that the functional diversity had a closer tie with stability than the species diversity. SEM did not find any direct effect of environmental factors on phytoplankton community stability, which rejected our hypothesis H2. Instead, SEM found that water temperature and phosphate decreased phytoplankton community stability by increasing the first principal component of the community-weighted means of traits (CWM_PC1), which supported hypothesis H3. Further analysis showed that the increased water temperature and phosphate concentration can promote “r-strategists” species (larger CWM_PC1), which are less resistant to environmental disturbances, therefore decreasing the phytoplankton community stability. Our study highlights the importance of functional diversity in maintaining the relationship between biodiversity and stability in the phytoplankton community, which may provide a mechanistic understanding of the biodiversity-stability relationships in aquatic ecosystems.